Development and testing of a new-generation aerosol exposure system: The independent holistic air-liquid exposure system (InHALES). (September 2020) - Steiner, Sandro; Herve, Pierre; Pak, Claudius; Majeed, Shoaib; Sandoz, Antonin; Kuczaj, Arkadiusz; Hoeng, Julia
Abstract: The dose of inhaled materials delivered to the respiratory tract is to a large extent a function of the kinetics of particle deposition and gas dissolution on or in the airway and lung epithelia, and therefore of the structural and functional properties of the respiratory tract. In vitro aerosol exposure systems commonly do not simulate these properties, which may result in the delivery of non-realistic, non-human-relevant doses of inhalable test substances to the in vitro biological test systems. We developed a new-generation in vitro aerosol exposure system, the InHALES, that can, like the human respiratory tract, actively breathe, operate medical inhalers, or take puffs from tobacco products. Due to its structural and functional similarity to the human respiratory tract, the system is expected to deliver human-relevant doses of inhalable materials to cell cultures representing respiratory tract epithelia. We here describe the proof of concept of the InHALES with respect to aerosol delivery and compatibility with oral, bronchial, and alveolar cell cultures. The results indicate that the system structure and function translate into complex patterns of test atmosphere delivery that, with increasing system complexity, may closely mimic the patterns observable in the human respiratory tract. Highlights: A physiology based in vitro aerosol exposure system was developed. It structurally and functionally simulates the human respiratory tract. It is expected to deliver in vivo relevant aerosol doses to cell cultures. This increases the toxicological relevance of aerosol exposures. Testing of a system prototype is demonstrated, providing a proof of concept.